2005
DOI: 10.1126/science.1117241
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-Feeding Plesiosaurs

Abstract: Elasmosaurid plesiosaurs were an important part of Cretaceous marine reptile communities and are generally considered to have been predators of small, agile, free-swimming fish and cephalopods. Two elasmosaurid specimens from Aptian and Albian deposits in Queensland, Australia, include fossilized gut contents dominated by benthic invertebrates: bivalves, gastropods, and crustaceans. Both specimens also contained large numbers of gastroliths (stomach stones). These finds point to a wider niche than has previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 8 publications
1
46
1
1
Order By: Relevance
“…These sand grains may have two different sources: 1) a larger sandstone clast(s) that disintegrated in the stomach; 2) relatively coarse sediment ingested intentionally, or accidentally (e.g., during feeding on benthic prey). Accidental ingestion is consistent with evidence suggesting that long-necked plesiosaurians may have been specialised predators of invertebrates dwelling on or in seabed sediments (McHenry et al 2005;Geister 1998). …”
Section: Gastric Contentsupporting
confidence: 65%
See 2 more Smart Citations
“…These sand grains may have two different sources: 1) a larger sandstone clast(s) that disintegrated in the stomach; 2) relatively coarse sediment ingested intentionally, or accidentally (e.g., during feeding on benthic prey). Accidental ingestion is consistent with evidence suggesting that long-necked plesiosaurians may have been specialised predators of invertebrates dwelling on or in seabed sediments (McHenry et al 2005;Geister 1998). …”
Section: Gastric Contentsupporting
confidence: 65%
“…They are located in an area under the dorsal ribs, between the pectoral and pelvic girdles at the level of the midpoint of the trunk. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 with plesiosaurians, they have been mainly documented in elasmosaurids (e.g., Welles and Bump 1949;Everhart 2000;Schmeisser and Gilette 2009;McHenry 2005;Sato et al 2006;Kubo et al 2012). Only two occurrences have been reported for Lower Jurassic taxa (Taylor 1993;O'Keefe et al 2009).…”
Section: Gastric Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples from the Cretaceous are also known. In addition to a decapod carapace, McHenry et al (2005) mentioned that stomach contents of an Early Cretaceous (Albian) plesiosaur contained crustacean fragments while Sanz et al (1996) reported Early Cretaceous (Barremian) birds yielded crustacean remains, also in the stomach region.…”
Section: Predation Of Crustaceansmentioning
confidence: 99%
“…TROPHIC INTERACTIONS between Mesozoic marine vertebrates have been reconstructed from preserved gut contents (e.g., Pollard 1968, Wilby & Martill 1992, Maisey 1994, Shimada 1997, Sato & Tanabe 1998, Cicimurri & Everhart 2001, Everhart 2004a, McHenry et al 2005, Kear 2006, Martin & Fox 2007, O'Keefe et al 2009), coprolites (e.g., Martin & Kennedy 1988, Maisey 1994, Kear 2006, Everhart 2007, Everhart et al 2010, Harrell & Schwimmer 2010, Eriksson et al 2011, regurgitates (e.g., Hattin 1996, Oji et al 2003, Salamon et al 2012, broken shells/ bones/teeth (e.g., Lingham-Soliar 2004, Zatón & Salamon 2008, Vullo 2011 and, most evocatively, bite marks (e.g., Kauffman & Kesling 1960, Kauffman 1972, Martill 1990, Ward & Hollingworth 1990, Neumann 2000, Kear & Godthelp 2008, Klompmaker et al 2009, Kellner et al 2010, Kauffman & Swado 2013. Because bite traces directly reflect the actions of living animals, they can also provide information on behaviours such as feeding strategies and social activities.…”
mentioning
confidence: 99%